2011
DOI: 10.1016/j.jsat.2010.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Unintended pregnancy in opioid-abusing women

Abstract: The aim of the present study was to estimate the prevalence of unintended pregnancy and its three subtypes (mistimed, unwanted, ambivalent) among opioid-abusing women. In the general population, 31–47% of pregnancies are unintended; data on unintended pregnancy in opioid- and other drug-abusing women are lacking. Pregnant opioid-abusing women (N=946) screened for possible enrollment in a multi-site randomized controlled trial comparing opioid maintenance medications completed a standardized interview assessing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
192
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 233 publications
(203 citation statements)
references
References 9 publications
5
192
1
5
Order By: Relevance
“…Overall, there is limited research relating to the SRH needs of women with SUDs. An American study found that of 956 women who used opioids, 86% of these women had a previous unintended pregnancy (compared to 31-74% of the general population) (Heil et al, 2011). Another study of 204 women enrolled in drug treatment programs in Australia, found these women had higher birth rates than the general population, more unplanned pregnancies, and more pregnancies at a younger age (<18), higher rates of miscarriage stillborn and abortion compared to National data (Black, Stephens, Haber, & Lintzeris, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, there is limited research relating to the SRH needs of women with SUDs. An American study found that of 956 women who used opioids, 86% of these women had a previous unintended pregnancy (compared to 31-74% of the general population) (Heil et al, 2011). Another study of 204 women enrolled in drug treatment programs in Australia, found these women had higher birth rates than the general population, more unplanned pregnancies, and more pregnancies at a younger age (<18), higher rates of miscarriage stillborn and abortion compared to National data (Black, Stephens, Haber, & Lintzeris, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Schwarz et al (2007) found that ambivalent women were older and more frequently non-white when compared with women with a positive attitude towards getting pregnant. Heil et al (2011) found that ambivalently pregnant women were older, more frequently non-white, and less often employed when compared with women with an intended pregnancy. McQuillan, Greil, and Shreffler (2011, see Table 1) found that women who were "okay either way" about getting pregnant (i.e., indifferent) fell between those trying to get pregnant and those trying not to get pregnant on a number of demographic variables, including age (the group trying to get pregnant was youngest), marital status (the group trying to get pregnant was most often married), parity (the group trying to get pregnant had fewer children), race/ethnicity (the group trying to get pregnant was most often Hispanic and least often white), and education (the group trying to get pregnant was most educated).…”
Section: Hypothesesmentioning
confidence: 97%
“…However, there are three recent papers in which researchers who make use of a midpoint definition of ambivalence (Heil et al 2011;Schwarz et al 2007) or indifference (McQuillan, Greil, and Shreffler 2011) report some results on the relationship between selected demographic variables and their measure of ambivalence/indifference. Schwarz et al (2007) found that ambivalent women were older and more frequently non-white when compared with women with a positive attitude towards getting pregnant.…”
Section: Hypothesesmentioning
confidence: 99%
“…Many authors (see for example Barnard & McKeganey, 2004;Economidoy, Klimi, & Vivilaki, 2012;Heil et al, 2011;Poole, 2009;Wright, Schuetter, Fombonne, Stephenson, & Haning, 2012) have associated AOD with increased risk of health and social problems such as liver disease, blood born viruses, high blood pressure, anaemia, malnutrition, poverty, mental health disorders, arrests, incarceration and unplanned pregnancy. Alcohol and other drug using women are also particularly susceptible to sexually transmitted infection including Human Papilloma Virus (HPV), which is now well known to be present in 99.7% of cervical cancers (Sikström, Hellberg, & Nilsson, 1995).…”
Section: Introductionmentioning
confidence: 99%